2000
DOI: 10.1093/treephys/20.8.503
|View full text |Cite
|
Sign up to set email alerts
|

Genes expressed in the latex of Hevea brasiliensis

Abstract: Rubber (cis-1,4-polyisoprene), an important raw material for many industrial uses, is synthesized in the latex of Hevea brasiliensis (Willd. ex A. Juss.) Müll. Arg. We postulated that the genes uniquely or preferentially expressed in the latex may be important for rubber biosynthesis. We constructed cDNA libraries from the latex of H. brasiliensis to investigate the genes expressed in the latex by single-run partial sequencing of the cDNA clones. Sequence analyses identified 245 expressed sequence tags (ESTs),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 33 publications
1
30
0
1
Order By: Relevance
“…The size of Myb and TCTP genes was 970 and 670 bp, respectively. The sequences were similar to the Myb and the TCTP genes reported earlier (Chen et al 2003;Han et al 2000). As predicted from the SSH results and RT-PCR (Fig.…”
Section: Validation Of Diverential Expressionsupporting
confidence: 86%
“…The size of Myb and TCTP genes was 970 and 670 bp, respectively. The sequences were similar to the Myb and the TCTP genes reported earlier (Chen et al 2003;Han et al 2000). As predicted from the SSH results and RT-PCR (Fig.…”
Section: Validation Of Diverential Expressionsupporting
confidence: 86%
“…Both analyses showed that the mRNA transcript accumulation was decreased by 2-5 folds in TPDaffected tree, compared to healthy one. It is interesting to note that the accumulation of HbTOM20 mRNA transcript level in different clones (PB217 [ PB235 [ RRII105) is proportional to the percent of TPD occurrence of these clones: PB217 (5-10) [ PB235 (10)(11)(12)(13)(14)(15) [ RRII105 (15)(16)(17)(18)(19)(20) [3]. As expected, the HbTOM20 mRNA transcripts level was significantly down-regulated in TPD-affected trees of all the clones tested (Fig.…”
Section: Expression Analysis By Semi-quantitative Rt-pcr and Northernmentioning
confidence: 99%
“…The latex of Hevea is a rubber containing cytoplasm expelled from the laticifers, upon controlled bark wounding or tapping. When severed during tapping, high turgor pressure inside the laticifers expels latex which contains 30-50% of cis-1,4 polyisoprene [15]. The laticifers are periodically emitted from the cambium as single cells, forming latex cell mantels in the soft bark of the rubber tree [11].…”
mentioning
confidence: 99%
“…Teknik rekayasa genetika pada tanaman karet semakin lebih mudah dilakukan dengan telah berhasil disusunnya konsep genom (Rahman et al, 2013) dan pustaka cDNA dari lateks (Han et al, 2000;Chotigeat et al, 2010). Hasil penelitian tersebut menunjukkan jumlah gen diperkirakan sebesar 68.955 gen, dan 12,7 % dari jumlah gen tersebut merupakan gen unik pada Hevea.…”
Section: Rekayasa Genetikaunclassified